2010
DOI: 10.4103/0377-4929.64333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic-resistant Acinetobacter baumannii in a 1000-bed tertiary care hospital in Tehran, Iran

Abstract: Acinetobacter baumannii is a ubiquitous pathogen that has emerged as a major cause of healthcare-associated infections. Acinetobacter baumannii usually causes respiratory tract, urinary tract, blood stream and surgical site infections. They are of increasing importance because of its ability to rapidly develop resistance to the major groups of antibiotics. There are few data available on the antimicrobial susceptibility of A. baumannii in Iran. During the period of study from July 2005 to November 2006, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
18
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 0 publications
11
18
3
Order By: Relevance
“…The sex distribution is comparable and is in concordance with a study done by Rahbar et al 12 . This may be attributed to the fact that health care -associated infections do not have a discernible sex predilection.…”
Section: Sample Processingsupporting
confidence: 81%
See 4 more Smart Citations
“…The sex distribution is comparable and is in concordance with a study done by Rahbar et al 12 . This may be attributed to the fact that health care -associated infections do not have a discernible sex predilection.…”
Section: Sample Processingsupporting
confidence: 81%
“…In India, very few studies on Acinetobacter species have been reported and in view of their increasing importance in nosocomial infections, further studies are warranted in this part of world. In our study prevalence of Acinetobacter baumannii was 33%, which was comparable to many studies 9,11,12,15 in which the prevalence was reported to be in the range of 28% to 36%. .…”
Section: Sample Processingsupporting
confidence: 76%
See 3 more Smart Citations